Geometric Attributes of Polygonal Crack Patterns in Columnar Joints. Issue 5 (12th May 2021) - Akiba, Y.; Takashima, A.; Inoue, A.; Ishidaira, H.; Shima, H.
Abstract: A well‐ordered polygonal crack pattern is frequently observed on the outcrop surface of columnar joints. The crack pattern's geometry and topology result from the volume contraction of solidified lava during thermal dissipation. In this study, we conducted field measurements of columnar joints at four different sites with various lithologies in Japan to understand the influence of geography and lithological character on their geometric characteristics. Drone‐aided photography and computer‐based image analysis enabled us to examine the constituent polygons' geometric attributes and their statistics with high accuracy. This methodology revealed a relationship between the geometry and topology of the polygonal crack patterns. Moreover, we established a positive correlation between the polygon area and the number of vertices of a polygon at each study site, irrespective of lithology, or geographic position. These results are consistent with previous investigational studies, in particular starch‐based analog experiments. Plain Language Summary: "Gallery of rock prisms carved by Nature" When erupted lava is rapidly cooled by seawater, numerous cracks penetrate inward, resulting in a splendid landscape called "columnar jointing." It is a mysterious aggregate of prismatic rocks with polygonal (often hexagonal) cross‐sections, the most famous example being Giant's Causeway in Ireland. Careful examination of columnar jointing over several localities has revealed several scientific laws hidden behind these joints' shapes. First, there is a relationship between the type of polygon in the cross‐section and its area. When the area is small, the shape tends to be a pentagon; but if the area is medium or large, the shape is likely to be a hexagon or heptagon, respectively. Interestingly, this tendency holds regardless of the rocks' locality, chemical character, or the prism's length scale. Second, the extent to which the polygons shape is distorted is not random but is kept below a threshold. Again, this threshold's magnitude is universal and independent of the locality, character, and prism scale. These two findings imply an unknown mechanism governing how Nature carves these magnificent prismatic sculptures during the rapid cooling of lava. Key Points: A drone was used to obtain aerial images of polygon patterns on columnar joints' outcrop surfaces at four different sites in Japan Unexpected correlations between geometrical characteristics of the cross‐section of prisms were revealed by image processing Conclusions obtained from field measurements were consistent with those of analog experiments based on starch slurry